Enhancement of recovery stresses of the Ni-50.2Ti alloy by severe plastic deformation using a high-ratio differential speed rolling technique. (November 2016) - Lim, Y.G.; Han, S.H.; Choi, E.S.; Kim, W.J.
Abstract: The Ni-50.2Ti alloy was severely plastically deformed by differential speed rolling with high speed ratios in range of 2–4.2. The maximum recovery and residual recovery stresses, which are important for applications in civil engineering, were improved after rolling. This result was attributed to the significant increase in the strength of the martensite phase and the large decrease in martensitic transformation finish temperature ( M f ) by microstructural refinement. Post-deformation annealing at 673 K deteriorated the shape memory properties, which was attributed to the formation of a martensitic R -phase in the alloy and an increase in the M f temperature. Graphical abstract: